A new block cipher based on finite automata systems - Khaleel, Ghassan; Turaev, Sherzod; Mohd Tamrin, Mohd Izzuddin; Alshaikhli, Imad Fakhri Taha (IIUM Press, 2016)
The performance and security have central importance of cryptography field. Therefore, the need to use block ciphers are become very important. This paper presents a new block cipher based on finite automata system. The proposed cryptosystem is executed based on parallel computations to reduce the delay time. Moreover, to achieve high security, we use different machines (variant non-deterministic automata accepters) as keys for encryption and decryption.